Implementing Objective-Centric ERM in Charities. Issue 6 (1st December 2016) - Byrne, Angela
Abstract: Escalating expectations in the private sector for Enterprise Risk Management (ERM) are trickling down to charities. Sophisticated public donors and government funders are increasingly seeking evidence and accountability that risks are being managed effectively. The focus on risk management practices is expected to continue as ERM continues to be recognized as a core element of well-managed organizations. While there are growing calls for ERM in charities they are challenged to find an approach that fits their environment and produces value while making the best use of scarce resources. The article discusses emerging research on the limitations of risk-centric approaches and promotes a proven alternative that makes good sense for charities. It recommends a model called Board & C-Suite Driven/Objective Centric ERM developed by Tim Leech of Risk Oversight Solutions. The article demonstrates how the Board & C-Suite Driven/Objective Centric ERM was implemented at the Ottawa Humane Society (OHS). It discusses why the approach made good sense for OHS and the challenges in implementation. The article concludes with important lessons for charities implementing or strengthening risk management frameworks.